The economics of strategic opportunity - Jerker Denrell; Christina Fang; Sidney G. Winter (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2003)
As emphasized by Barney (1986), any explanation of superior profitability must account for why the resources supporting such profitability could have been acquired for a price below their rent generating capacity. Building upon the literature in economics on coordination failures and incomplete markets, we suggest a framework for analyzing such strategic factor market inefficiencies. Our point of departure is that a strategic opportunity exists whenever prices fail to reflect the value of a resource's best use. This paper examines the challenges of imputing a resource's value in the absence of explicit price guidance and suggests the likely characteristics of strategic opportunities. Our framework also suggests that the discovery of strategic opportunity is often a matter of serendipity and access to relevant idiosyncratic resources. This latter observation provides prescriptive advice, although the analysis also explains why more detailed guidance has to be firm specific.
Keywords: 330; Theorie der Unternehmung; Strategisches Management